The Ethical Dilemma of Digital Necromancy: The Elis Regina Case and a Partial Solution by Brazilian Legislators (Revista Iberoamericana de Bioética, 2024)
The combination of death and technology is a tricky topic, especially with Artificial Intelligence (AI) thrown into the mix, as seen in the Elis Regina Case in Brazil. Volkswagen used AI to bring back the late singer’s image for a commercial, which sparked debates nationwide and globally about the ethical and legal implications of AI resurrecting deceased individuals’ images, dubbed “digital necromancy”. Efforts such as Bill No. 3592/23 aim to regulate postmortem image use, requiring explicit consent or presuming its prohibition. This paper explores the bioethical dimensions raised by the case, diving into the ethical dilemmas and legal responses while shedding light on the evolving landscape of bioethics and law in the age of advancing technology. Using a case study, this paper concludes that Bill No. 3592/23 offers a partial solution to a complex ethical dilemma, opening a possible pathway for future regulators.
Keywords: artificial intelligence; law and bioethics; digital necromancy; Elis Regina; negative presumption